Analysis of Mathematical Reasoning Ability In Terms of Students’ Mathematical Learning Independence - Hasna, Annisa; Maimunah, Maimunah; Suanto, Elfis (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Mathematical reasoning is one of the important mathematical abilities possessed by students. This ability can be improved through mathematical learning independence. Mathematical learning independence is currently not visible in conventional learning from teachers. Low mathematical learning independence makes students' mathematical reasoning abilities also not realized properly. The purpose of this study was to describe students' mathematical reasoning abilities in terms of mathematical learning independence of MAN 2 Pekanbaru students. The research method is a qualitative approach with data collection techniques in the form of mathematical reasoning ability tests and mathematical learning independence questionnaires. This study found that the mathematical reasoning abilities of students with high mathematical learning independence were better than students with medium and students with medium mathematical learning independence were better than students with low mathematical learning independence.